Air Transport and Operations Proceedings of the Third International Air Transport and Operations Symposium 2012 - Curran, Prof. R (IOS Press, 2014)
The focus of the Air Transport and Operations Symposium 2011 was about industry and academia considering how air transport should evolve in order to optimise its value in the 21st Century! Slowly but surely, countries are climbing out of the economic recession and growth rates are positive. The aerospace industry can now be very positive about recovery but in that pioneering spirit of the past, needs to focus more than ever on sustaining value in order to evolve faster in the right direction in this transition time of added opportunity; when we can emulate the pioneers of the past! The opportunity that lies in front of us includes other key aerospace performance challenges, such as the Single European Sky ATM Research (SESAR)’s aims in being able to handle a threefold increase in capacity, improving safety by a factor of 10, reducing environmental impact by 10% and reducing expenses by a half.